2017
DOI: 10.1016/j.actbio.2017.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of collagen denaturation in decellularized tissues using a collagen hybridizing peptide

Abstract: Decellularized extracellular matrix (ECM) derived from tissues and organs are emerging as important scaffold materials for regenerative medicine. Many believe that preservation of the native ECM structure during decellularization is highly desirable. However, because effective techniques to assess the structural damage in ECM are lacking, the disruptive effects of a decellularization method and the impact of the associated structural damage upon the scaffold’s regenerative capacity are often debated. Using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 62 publications
(104 reference statements)
5
94
0
Order By: Relevance
“…Previous reports have demonstrated that disruption of ECM components following decellularization/antigen removal processes has potential to result in innate immune system activation [6,26,32,41], resulting in fibrous encapsulation and foreign body response [18,33,42]. In the current study, GFBP implants resulted in marked innate immune activation and resultant fibrous encapsulation.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Previous reports have demonstrated that disruption of ECM components following decellularization/antigen removal processes has potential to result in innate immune system activation [6,26,32,41], resulting in fibrous encapsulation and foreign body response [18,33,42]. In the current study, GFBP implants resulted in marked innate immune activation and resultant fibrous encapsulation.…”
Section: Discussionsupporting
confidence: 48%
“…This distinction suggests that the innate immune response is tolerant to minute deviations in ECM protein organization provided proteins are not denatured. Other literature also observed this phenomenon when examining the innate immune response to collagen denaturation [32,41,47]. For example, harsh decellularization methods (e.g., SDS) have been previously documented to result in significant ECM damage.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This study demonstrated increased CHP staining, as a direct measure of damage to the triple helical structure of collagen molecules, in the H-AGE female group, which may also account for the reduced SHG intensity. Alterations in fibril packing can increase the susceptibility to enzymatic digestion (McBride et al, 1997) and collagen degradation, which in turn can contribute to the loss of collagen SHG intensity (Hwang et al, 2017). It has been proposed that AGE crosslinking can lead to mechanically induced breakdown of the collagen triple helical structure by causing forces, transmitted through the intermolecular AGE crosslinks, to accelerate enzyme degradation (Bourne et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…PMMA embedded mid-sagittal lumbar sections were stained using Collagen Hybridizing Peptide-biotin conjugate (B-CHP; BIO300, 3Helix Inc; Salt Lake City, UT, USA) to detect the presence of collagen damage as described by (Hwang et al, 2017, Zitnay et al, 2017. This procedure includes the creation of a 2 µM CHP solution, heating of the solution at 80°C for 5 minutes to monomerize the peptides, quenching in an ice bath for 30 seconds, and application of the solution to the tissue.…”
Section: Molecular Assessment Of Collagenmentioning
confidence: 99%